The Scientific Miracles of Olive (Zaitūn) in the Qur'an: Perspectives of Classic and Scientific Interpretations - Ahmad Atabik (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Today, commentators use scientific interpretation to investigate various types of knowledge presented by the Qur’an, such as some modern commentators combine scientific studies of fruits cited in the Qur’an with their medicinal properties, such as olives (Olea Europea). According to Al-Baqi, there are at least 7 (seven) verses that mention ‘Zaitūn’ (olives), which are spread across seven different letters. The purpose of this article is to dissect the anatomy of classical and scientific interpretations of the olive fruit in the Qur'an. In the scope of library research, this study employed a thematic method that refers to the literature on commentary books, scientific miracles books of the Qur’an about fruits, and articles in reputable journals. According to the findings of this study, olives are known as the name of a blessed fruit that has advantages over other fruits in several interpretations of the Qur'an. There are various interpretations of the word ‘Zaitūn’; some argue that it refers to the location where many figs and olives grow, namely Jerusalem, where Prophet Isa was born and received revelation. Whereas, scientific interpretation reveals that olives are effective as herbal medicines capable of treating a variety of diseases such as treating the digestive tract in general (particularly the liver), lowering the risk of high blood pressure, treating joint problems in both hands, and lowering the risk of cancer.